Eneolitization of the Forest Steppe Volga Region: cultural evolution or migration? - Arkadii I. Korolev (Археология евразийских степей)
The source base for the Eneolithic of the forest steppe Volga region includes Eneolithic burial grounds and campsites. The data from the study of ceramics, stone, bone, metal tools, anthropological and archeozoological materials, radiocarbon dating were used. The purpose of the work is to clarify the place of materials from the Late Neolithic of the forest steppe Volga region in the process of changing the Neolithic to the Eneolithic. The results of radiocarbon dating confirmed the presence of a common time interval for the Late Neolithic – Early and Middle Eneolithic. The analysis of ceramics and stone tools showed that the Neolithic substrate is well expressed in the ceramics of the Samara culture of the early stage and, to a lesser extent, the Ivanovo stage. Stone tools keep the traditions of the Caspian culture. The influence of the forest steppe Neolithic in ceramics and stone tools of the Khvalynsk culture has not been revealed. Local Neolithic traditions are most fully represented in pottery and stone tools of the Lebyazhinka, Tok, Chekalino types. The Eneolithic features such as collared ceramics, tools made of large flint and quartzite blades, large burial grounds, cattle-breeding, copper items, stone scepter finials is associated with the Samara and Khvalynsk cultures.